1997
DOI: 10.3109/03005364000000007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Childhood Sensorineural Hearing Loss in the Oxford Region

Abstract: We have used a comprehensive register of hearing-impaired children born in the former Oxford Health Region to study risk factors for sensorineural hearing loss. The occurrence of a wide variety of risk factors was documented from the case notes of 145 children; these were all the cases known at the time of the study with all degrees of hearing loss born between 1984 and 1988. Comparison with the normal Regional population showed that maternal age over 35 years and Asian ethnic origin were significant risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…The level of deprivation 36 and Asian ethnic background 13 are both factors that have been found to increase the odds ratio for PCHI within a community, and inward flow of children into the district from abroad after the newborn or infant screens, and before school entry, are characteristics that are not uniform nationwide. Nevertheless, they are pertinent to the wider interpretation of the current data.…”
Section: Generalising the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The level of deprivation 36 and Asian ethnic background 13 are both factors that have been found to increase the odds ratio for PCHI within a community, and inward flow of children into the district from abroad after the newborn or infant screens, and before school entry, are characteristics that are not uniform nationwide. Nevertheless, they are pertinent to the wider interpretation of the current data.…”
Section: Generalising the Studymentioning
confidence: 99%
“…All studies received an 'unclear' for this question as none of them clearly states what data were available to them at the time of testing. [30][31][32][33][34][35][36][37]. The two-by-two tables for sensitivity and specificity, where available, are presented in Appendix 10.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Several studies have shown that children who at birth had very low birth weight have increased risk of severe hearing impairment. [13][14][15] Less attention has been given the association between birth weight and hearing impairment in general taking into consideration other pregnancy-related conditions, which may represent causal factors in the development of hearing. A large and representative population is therefore required to assess the effects of birth weight per se.…”
mentioning
confidence: 99%
“…We also considered a perinatal risk factors: cranio-facial abnormality, birth weight <1500 g, hyperbilirubinaemia, low apgar scores, mechanical ventilation !5 days and neonatal intensive care >48 h [8,[31][32][33]. In this way we were able to divide all the newborns into two groups: newborn with risk factor and newborn without risk factor.…”
Section: Methodsmentioning
confidence: 99%
“…Hearing loss is one of the commonest disorders present at birth; the literature report a large range of childhood hearing impairment (PCHI) from 0.7 to 4.2/1000 live births [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]; it is probably due to many elements that each author studied: unilateral or bilateral hearing loss; severity of hearing loss; age, sex, ethnicity and socio-economic status in a particular population; presence in the group observed of prenatal and perinatal risk factors.…”
Section: Introductionmentioning
confidence: 99%